Stereoselective Ammonium-Directed Epoxidation in the Asymmetric Syntheses of Dihydroconduramines (–)-A-2, (–)-B-2, (–)-C-3 and (+)-F-3 - Da Silva Pinto, Solange; Davies, Stephen G.; Fletcher, Ai M.; Roberts, Paul M.; Thomson, James E. (Synthesis, 2018)
Epoxidation of racemic trans-2-(N,N-dibenzylamino)cyclohex-3-en-1-ol, upon treatment with Cl3CCO2H then m-CPBA, proceeded with poor diastereoselectivity (ca. 60:40 dr), whilst epoxidation of racemic trans-2-(N-benzylamino)cyclohex-3-en-1-ol under the same conditions proceeded with high diastereoselectivity (>95:5 dr) and was followed by completely regioselective and stereospecific ring-opening in situ to give, after methanolysis of the intermediate trichloroacetate ester, (1RS,2SR,3SR,4SR)-2-(N-benzylamino)cyclohexane-1,3,4-triol. Use of aq HBF4 as the acid protecting agent gave the amino triol directly. The differing diastereoselectivities of these epoxidation reactions may be due to a predilection towards formation of an intramolecular hydrogen-bond in the former substrate disrupting the ability of the in situ formed ammonium moiety to act as a directing group for the incoming oxidant; the presence of two potential hydrogen-bond donors (i.e., two N–H bonds) in the latter substrate circumvents this limitation. With the criterion for a highly diastereoselective (ammonium-directed) epoxidation in this system established, a synthesis of enantiopure trans-2-(N-benzylamino)cyclohex-3-en-1-ol (>99% ee) was developed and the ammonium-directed epoxidation was then employed as a key synthetic step to facilitate the asymmetric syntheses of enantiopure dihydroconduramines (–)-A-2, (–)-B-2, (–)-C-3 and (+)-F-3 (>98% ee in each case) from 1,3-cyclohexadiene.
Keywords: amino alcohols; asymmetric synthesis; chemoselectivity; diastereoselectivity; epoxidation; regioselectivity; ring-opening; stereoselective synthesis